A Novel PCNT Frame Shift Variant (c.7511delA) Causing Osteodysplastic Primordial Dwarfism of Majewski Type 2 (MOPD II) - Dehghan Tezerjani, Masoud; Vahidi Mehrjardi, Mohammad Yahya; Hozhabri, Hossein; Rahmanian, Masoud (Frontiers in Pediatrics, 2020)
Background: Microcephalic osteodysplastic primordial dwarfism type II (MOPD II) is an autosomal recessive and skeletal disorder included wide spectrum of clinical abnormalities such as fetal growth restriction, disproportionate face, microcephaly, post-natal growth retardation, adult height under 100cm, abnormal skin pigmentation, insulin resistance, and susceptibility to cerebrovascular and hematologic abnormalities. Due to heterogeneous feature of MOPDs diseases and common clinical features among the different subtypes, mutation analysis can be considered as fundamental in the accurate diagnosis and confirmation of the MOPDII disease. Some studies revealed that, variants of gene encoding Pericentrin protein, PCNT, were associated with MOPDII. Methods: We performed whole exome sequencing based on the next generation sequencing (Illumina platform), to perform correct diagnosis in a 17-year-old girl with an unknown disease who was referred to the Diabetes Research Center in Yazd, Iran. The clinical features of the patient were short stature, generalized brachydactyly, gradual deterioration of brain functioning, menstrual irregularity, clitoromegaly, acanthosis nigricans, diabetes mellitus, hyperinsulinemia, insulin resistance, and dyslipidemia. Accordingly, her parents were also first cousin with no background disease. After identifying the novel variant, it was confirmed in the proband and her family using bi-directional Sanger sequencing, and its pathogenicity was also checked by different online tools. Results: Our study revealed a novel frame-shift variant in PCNT gene (c.7511delA, p.K2504Sfs*27), which causes premature termination of Pericentrin protein. The result disclosed that, the proband was affected by MOPDII disease. In addition, the Sanger sequencing confirmed the novel homozygote variant in the proband and heterozygote one in her parents, and the extended family perfectly segregated among them. Online tools such as Varsome and MutationTaster also showed a high level of pathogenicity for the variant identified. Conclusion: A novel variant was identified in the proband and her extended family, which emphasized the importance of PCNT gene mutations analysis in the screening and accurate identification of MOPD II disease, especially in prenatal diagnosis.